Knowledge Level of Family about Risk Factor and Early Detection of Stroke Patient at Public Regional Hospital dr. Loekmonohadi Kudus - Noor Faidah; Lugitah Lilian Sari; Emma Setiyo W; Nila Putri Purwandari (Universitas STRADA Indonesia, 2026)
Stroke is a serious health problem and a leading cause of disability and death, with incidence rates continuing to increase. Families who live with stroke patients often delay treatment because they lack adequate understanding of stroke risk factors and early warning signs. Knowledge of risk factors and symptoms influences the actions that families take before and during transportation to the hospital, as understanding these factors can lead to quicker recognition of a stroke and prompt medical attention. Stroke severity and clinical outcomes can worsen with delayed treatment. Indonesia had 8.3 strokes per 1,000 people in 2023, according to the Indonesian Health Survey. This study examined stroke patients' families' knowledge of risk factors and early stroke symptom detection at RSUD dr. Loekmono Hadi Kudus. This study employed a quantitative descriptive design with a cross-sectional approach. The research was conducted in June 2025 at the Neurology Outpatient Clinic of RSUD dr. Loekmono Hadi Kudus. The study included 490 family members of clinic-treated ischemic and hemorrhagic stroke patients. Researchers used purposive sampling to select 49 respondents. A modified Stroke Recognition Questionnaire (SRQ) was used to collect data, and univariate analysis was used to analyze it. The findings indicated that 53.1% of respondents possessed a moderate understanding of stroke risk factors and the early identification of stroke symptoms, 26.5% exhibited inadequate knowledge, and merely 20.4% demonstrated proficient knowledge. These findings indicate that most families possess basic understanding, but gaps remain in accurate and timely detection.Most families of stroke patients at RSUD dr. Loekmono Hadi Kudus demonstrated a moderate level of knowledge regarding stroke risk factors and early detection of stroke symptoms.